Effects of backpack carriage on dual-task performance in children during standing andwalking - Beurskens, Rainer; Mühlbauer, Thomas; Grabow, Lena; Kliegl, Reinhold; Granacher, Urs (Journal of motor behavior, 2016)
Primary school children perform parts of their everyday activities while carrying school supplies and being involved in attention-demanding situations. Twenty-eight children (8-10 years old) performed a 1-legged stance and a 10 m walking test under single- and dual-task situations in unloaded (i.e., no backpack) and loaded conditions (i.e., backpack with 20% of body mass). Results showed that load carriage did not significantly influence children's standing and walking performance (all p > .05), while divided attention affected all proxies of walking (all p < .001). Last, no significant load by attention interactions was detected. The single application of attentional but not load demand negatively affects children's walking performance. A combined application of both did not further deteriorate their gait behavior.
Gesehen am 11.05.2020